Cultural Sensitivity and Global Pharmacy Engagement in Africa - Drame, Imbi (Am J Pharm Educ, 2019)
Global engagement between schools and colleges of pharmacy in the United States and Africa is increasing. For a balanced and fruitful engagement, sensitivity towards the cultural and clinical needs of the people and professionals of the African region is critical. In this paper, we have divided the discussion into Southern, East, Central, and West Africa. General information about Africa, with unique aspects for individual subregions and countries, will be introduced. Stereotypes and misconceptions about the region and the people will also be discussed, along with recommendations for culturally sensitive engagement for pharmacy and other health care practitioners when hosting members from, or visiting this region. The paper is a resource for schools and colleges of pharmacy who are currently engaged or considering future outreach opportunities in Africa.